Burning Bridges: The Automated Facial Recognition Technology and Public Space Surveillance in the Modern State - Zalnieriute, Monika (Science and Technology Law Review, 2021)
Live automated facial recognition technology, rolled out in public spaces and cities across the world, is transforming the nature of modern policing. R (on the application of Bridges) v Chief Constable of South Wales Police, decided in August 2020, is the first successful legal challenge to automated facial recognition technology in the world. In Bridges, the United Kingdom’s Court of Appeal held that the South Wales Police force’s use of automated facial recognition technology was unlawful. This landmark ruling could influence future policy on facial recognition in many countries. The Bridges decision imposes some limits on the police’s previously unconstrained discretion to decide whom to target and where to deploy the technology. Yet, while the decision requires that the police adopt a clearer legal framework to limit this discretion, it does not, in principle, prevent the use of facial recognition technology for mass-surveillance in public places, nor for monitoring political protests. On the contrary, the Court held that the use of automated facial recognition in public spaces – even to identify and track the movement of very large numbers of people – was an acceptable means for achieving law enforcement goals. Thus, the Court dismissed the wider impact and significant risks posed by using facial recognition technology in public spaces. It underplayed the heavy burden this technology can place on democratic participation and freedoms of expression and association, which require collective action in public spaces. The Court neither demanded transparency about the technologies used by the police force, which is often shielded behind the “trade secrets” of the corporations who produce them, nor did it act to prevent inconsistency between local police forces’ rules and regulations on automated facial recognition technology. Thus, while the Bridges decision is reassuring and demands change in the discretionary approaches of U.K. police in the short term, its long-term impact in burning the “bridges” between the expanding public space surveillance infrastructure and the modern state is unlikely. In fact, the decision legitimizes such an expansion.